Ferroptosis in Intrahepatic Cholangiocarcinoma: IDH1105GGT Single Nucleotide Polymorphism Is Associated With Its Activation and Better Prognosis - Sarcognato, Samantha; Sacchi, Diana; Fabris, Luca; Zanus, Giacomo; Gringeri, Enrico; Niero, Monia; Gallina, Giovanna; Guido, Maria (Frontiers in medicine, 2022)
ObjectivesIntrahepatic cholangiocarcinoma (ICC) has a dismal prognosis and often demonstrates an anti-apoptotic landscape, which is a key step to chemotherapy resistance. Isocitrate dehydrogenase 1 or 2 ( IDH1-2 )-mutated ICCs have been described and associated with better prognosis. Ferroptosis is a regulated iron-mediated cell death induced by glutathione peroxidase 4 (GPX4) inhibition, and may be triggered pharmacologically. GPX4 is overexpressed in aggressive cancers, while its expression is inhibited by IDH1 R 132 C mutation in cell lines. We investigated tissue expression of ferroptosis activation markers in ICC and its correlation with clinical-pathological features and IDH1-2 status.Materials and MethodsWe enrolled 112 patients who underwent hepatic resection or diagnostic liver biopsy for ICC. Immunostaining for transferrin-receptor 1 and GPX4, and Pearls’ stain for iron deposits were performed to evaluate ferroptosis activation. Immunostaining for STAT3 was performed to study pro-inflammatory and anti-apoptotic landscape. Main IDH1-2 mutations were investigated in 90 cases by real-time polymerase chain reaction.ResultsGPX4 overexpression was seen in 79.5% of cases and related to poor histological prognostic factors (grading and perineural and vascular invasion; p < 0.005 for all) and worse prognosis (OS p = 0.03; DFS p = 0.01). STAT3 was expressed in 95.5% of cases, confirming the inflammation-related anti-apoptotic milieu in ICC, and directly related to GPX4 expression ( p < 0.0001). A high STAT3 expression correlated to a worse prognosis (OS p = 0.02; DFS p = 0.001). Nearly 12% of cases showed IDH1 105 GGT single nucleotide polymorphism, which was never described in ICC up to now, and was related to lower tumor grade ( p < 0.0001), longer overall survival ( p = 0.04), and lower GPX4 levels ( p = 0.001).ConclusionOur study demonstrates for the first time that in most inflammatory ICCs ferroptosis is not active, and its triggering is related to IDH1-2 status. This supports the possible therapeutic role of ferroptosis-inducer drugs in ICC patients, especially in drug-resistant cases.